99mTc-DPD myocardial uptake and regional longitudinal strain in aTTR amyloidosis cardiomyopathy. (4th February 2022) - Merli, E; Ricci Lucchi, G; Pontone, G; Cicchitelli, G; Del Giudice, E; Fabbri, E; Rubboli, A; Piovaccari, G
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND amyloid cardiomyopathy is characterized by a typical "apical sparing" pattern of systolic longitudinal strain (LS) as visualized by echocardiography. Strain is well preserved at the apex of the left ventricle (LV) with a gradient from apex to base and the greatest impairment in the basal segments. The reason of this distribution is not clear. It could be a function of different amount of amyloid deposition. SPECT images using Technetium 99m bone tracers have shown a distribution mimicking regional LS. PURPOSE to compare regional myocardial LS and myocardial distribution of 99m Technetium-DPD (99m Tc-DPD) uptake in patients affected by aTTR amyloidosis cardiomyopathy. METHODS between 2016-2021 70 patients referred to our Cardiology Unit with heart failure/shortness of breath on exertion and showing significant left ventricular hypertrophy at 2-D echocardiography underwent 99m Tc-DPD scintigraphy to test the presence of cardiac amyloid. Grade 2-3 myocardial uptake at 180 minutes in the absence of abnormalities in the analysis of serum free light chains and serum and urine protein electrophoresis with immunofixation was considered sufficient for the diagnosis of aTTR amyloidosis. When scintigraphy was positive a SPECT study was performed to obtain semi quantitative measurements of segmental myocardial uptake (expressed as % of total myocardial uptake). Regional mean count was calculated by using a 6 basal, 12 mid and 2 apical segmental model. All patients underwent standard and 2D speckle tracking echocardiography. Mean systolic LS was calculated for each of 18 segments and mean basal (6 segments), mean mid (6 segments) and mean apical (6 segments) LS was calculated. RESULTS 46/70 patients had a positive scan and fulfilled criteria for aTTR amyloidosis. 33/46 had SPECT analysis. Male/female ratio was 29/4, age = 80 ± 6 years; 9/33 aortic stenosis; 19/33 carpal tunnel; 25/33 wild-type aTTR (4/33 ongoing genetic test); LV mass-=228 ± 48 g/m2; RWT = 0, 73 ± 0, 14; EF= 53 ± 9; EF to GLS ratio= 5, 6 ±1, 8. ANOVA showed a significant difference between basal, mid and apical strain as well as between basal, mid and apical uptake (-5, 5 ± 4, 4; -9, 6 ± 3, 2; -15, 9 ± 5, 6; p < 0, 001; 55 ± 14; 62 ± 10; 51 ± 11; p = 0, 0019). Comparison between groups showed that mean LS at the apex was significantly lower compared to basal and mid mean LS (Bonferroni test, p < 0, 001) (Fig 1). Apical myocardial uptake was significantly lower compared to mid segment but not to basal (Bonferroni test, p = 0, 02, p = 0, 6 respectively) (Fig 1). Spearman's test showed a correlation between LS and myocardial 99m Tc-DPD uptake (p = 0, 01, Rho = 0, 24). CONCLUSIONS Our data show that in this group of patients with cardiac aTTR amyloidosis apical LS is significantly lower compared to basal and mid segments and apical myocardial 99m Tc-DPD uptake is significantly lower compared to mid segments; a correlation between myocardial 99m Tc-DPD uptake distribution and the degree of LS impairment is present.